Excomuniones y protestantismo : El caso del Valle del Cauca, 1930-1940 (2005)
ABSTRACT: The subject about excomunication in Colombia during this time was relationed with presence of the protestantism like dissenters, betwen someone, that was afected for spirituals punishments of the Catholic Church. This pains afected socially and politically to excomunicatiors. One way which the Catholic Church sanctioned to the dissenters was the excomunication. This punishment was one public declaraction for to put to the dissenters out the Church and to impose public scoffing. The effects were diferents depending of the places to excomunications and radicalization of excomunitioners, some people were exclutioned and marginated, but others to make use this event for to declare opnening like catholicism's opossitors. The protestantism did to make big contribution to the list of excomunications published in the Arquidiocesan bulletin in the 30 years, the principal reason was for practice civil marriage, reject infantil baptism, to enroll his sons in the protestants schools and to promote establish civil cemeteries.